A stability assessment tool for anaerobic codigestion. (1st April 2017) - Cook, Sherri M.; Skerlos, Steven J.; Raskin, Lutgarde; Love, Nancy G.
Abstract: Anaerobic codigestion allows for greater resource recovery from organic substrates and provides opportunities for more stable operation than mono-digestion. Despite these benefits, the adoption of codigestion is limited because it can introduce operational complexity and suffers from some of the same challenges as mono-digestion, such as ammonia inhibition and nutrient imbalances. There is a need for rapid and cost-effective assessments that can provide insight to design engineers as they explore the valorization of local organic waste streams and seek to maintain or improve digester stability. To address this need, we developed and tested a tool that can yield useful stability indicators, performance predictions, and substrate selection protocols for codigestion. This tool uses quantitative, empirical data on stability indicators within an assessment framework to evaluate a digester's process stability. The tool's accuracy was tested using real and simulated digester data, and the importance of the nitrogen and lipid composition of a substrate was identified. The resulting stability assessment tool improves our fundamental understanding of codigestion, provides a mechanism to reduce the number of experiments, and guides selection of appropriate substrate combinations that can maximize energy recovery during codigestion without compromising process stability. Graphical abstract: Highlights: A quantitative stability definition for anaerobic digestion is proposed. The stability assessment tool can evaluate real and simulated data. The tool was validated against full-scale and experimental literature data. The tool can be used for model-based experimentation and design. The tool can be used to maximize digestion benefits without compromising stability.